Cliniconeuropathologic findings of familial frontal lobe epilepsy in Shetland sheepdogs - Morita, T. (2002)
We examined an epileptic focus by electroencephalography (EEG) by using an international 10-20 electrode system in 11 Shetland sheep dogs affected with familial idiopathic epilepsy. We also performed an evaluation of the amino acids in the cerebrospinal fluid (CSF) and a pathologic examination of the brains of 8 dogs that died from status epilepticus. Continuous electroencephalography demonstrated that an epileptic focus was initially detected in the frontal lobe, particularly the internal area, and that paroxysmal foci developed diffusely in other lobes of affected dogs with recurrent convulsions. The EEG analyses indicated spike and sharp wave complexes, which were considered to be paroxysmal discharges. An increased value for glutamate or aspartate was found in the CSF of some epileptic dogs. Histologically, acute neuronal necrosis and astrocytosis were distributed predominantly in the cingulate cortex and internal area of frontal cortex, less frequently in other areas of the cerebrum. The results of this study suggest that, initially, the dogs have an epileptic focus in the frontal lobe, and that the focus extends gradually to other areas of the cerebrum. Based on the distribution of neuronal necrosis and astrocytosis, acute neuronal damage may be related to the superexcitation of neurons following epilepsy.